Using optical stimulation to study the developing thalamocortical circuit in mouse somatosensory cortex - Marques-Smith, A (2014)
Charting connectivity between neurons in the brain is one of the main goals of circuit neuroscience. Despite great advances in our understanding of cortical circuit organisation, comparatively little attention has been devoted to studying how the intricate cortical connectivity emerges. Current views are that early synaptic connectivity within the cortex and between thalamus and cortex is largely mediated via silent synapses. Early patterns of network activity synchronise firing in pre- and post-synaptic elements of circuits and promote correlated activity, enabling synaptic plasticity and maturation via unsilencing. However, little is known about which circuits may be in place to promote such patterns of activity. In my thesis I used optical stimulation and electrophysiology to clarify circuits involved in the maturation of the thalamocortical circuit in the mouse barrel cortex.